2005
DOI: 10.1113/expphysiol.2004.028654
|View full text |Cite
|
Sign up to set email alerts
|

Role of adrenergic receptors in the reflex diuresis in rabbits during pulmonary lymphatic obstruction

Abstract: The role of adrenergic receptors in the reflex diuresis in response to pulmonary lymphatic drainage was examined in anaesthetized, artificially ventilated New Zealand White rabbits. Pulmonary lymphatic drainage was obstructed by raising the pressure in a pouch created from the right external jugular vein. This pulmonary lymphatic obstruction results in a reflex increase in urine flow and sodium excretion. This reflex is abolished by renal denervation and by administration of L-NAME, a non-selective inhibitor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The caudal end of the SVC is on the right‐hand bottom corner, and the cranial end is in the opposite corner. Reproduced with permission from McCormick et al (2005).…”
Section: Effect Of Altering Oncotic Pressure On Rar Activitymentioning
confidence: 99%
“…The caudal end of the SVC is on the right‐hand bottom corner, and the cranial end is in the opposite corner. Reproduced with permission from McCormick et al (2005).…”
Section: Effect Of Altering Oncotic Pressure On Rar Activitymentioning
confidence: 99%
“…33 There are reports which show that the renal NO generation is mediated by activation of alpha-2 receptors. 34 These studies establish that sympathetic excitation can lead to NO generation by activation of nNOS through alpha-2 receptors. 34 Further evidences in support of these propositions are provided by the observations of Mount and Power 35 who demonstrated that in the kidney, NO was involved in promoting natriuresis and diuresis and Majid and Navar 36 who reported that NO was involved in pressure natriuresis.…”
Section: Discussionmentioning
confidence: 87%
“…34 These studies establish that sympathetic excitation can lead to NO generation by activation of nNOS through alpha-2 receptors. 34 Further evidences in support of these propositions are provided by the observations of Mount and Power 35 who demonstrated that in the kidney, NO was involved in promoting natriuresis and diuresis and Majid and Navar 36 who reported that NO was involved in pressure natriuresis. While evaluating the role of NO, it is emphasised that the NO generated may produce antinatriuresis and antidiuresis also depending upon its site of action and the existing sympathetic drive.…”
Section: Discussionmentioning
confidence: 87%